Biomechanical associates of performance and knee joint loads during a 70-90° cutting maneuver in subelite soccer players - McBurnie, A. J.; Dos' Santos, T.; Jones, P. A. (The Journal of Strength and Conditioning Research, 2021)
The aim of this study was to explore the "performance-injury risk" conflict during cutting, by examining whole-body joint kinematics and kinetics that are responsible for faster change-of-direction (COD) performance of a cutting task in soccer players, and to determine whether these factors relate to peak external multiplanar knee moments. 34 male soccer players (age: 20 ± 3.2 years; body mass: 73.5 ± 9.2 kg; height: 1.77 ± 0.06 m) were recruited to investigate the relationships between COD kinetics and kinematics with performance and multiplanar knee joint moments during cutting. Three-dimensional motion data using 10 Qualisys Oqus 7 infrared cameras (240 Hz) and ground reaction force data from 2 AMTI force platforms (1,200 Hz) were collected to analyze the penultimate foot contact and final foot contact (FFC). Pearson's or Spearman's correlations coefficients revealed performance time (PT), peak external knee abduction moment (KAM), and peak external knee rotation moment (KRM) were all significantly related (p < 0.05) to horizontal approach velocity (PT: p = -0.579; peak KAM: p = 0.414; peak KRM: R = -0.568) and FFC peak hip flexor moment (PT: p = 0.418; peak KAM: p = -0.624; peak KRM: p = 0.517). Performance time was also significantly (p < 0.01) associated with horizontal exit velocity (p = -0.451) and, notably, multiplanar knee joint loading (peak KAM: p = -0.590; peak KRM: p = 0.525; peak KFM: p = -0.509). Cohen's d effect sizes (d) revealed that faster performers demonstrated significantly greater (p < 0.05; d = 1.1-1.7) multiplanar knee joint loading, as well as significantly greater (p < 0.05; d = 0.9-1.2) FFC peak hip flexor moments, PFC average horizontal GRFs, and peak knee adduction angles. To conclude, mechanics associated with faster cutting performance seem to be "at odds" with lower multiplanar knee joint loads. This highlights the potential performance-injury conflict present during cutting.